2016
DOI: 10.1111/aor.12785
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption as a Contributor for Inflammatory Mediators Removal by Different Hemofiltration Membranes: A Pilot Study

Abstract: Atherosclerosis is an important predictor of mortality in patients with chronic kidney disease (CKD) and is associated with a wide inflammatory response. The aim of this study is to evaluate in vitro how different membranes can remove mediators associated with this pathology in a closed loop dialysis model. We performed experimental hemofiltration in vitro using three different membrane materials. Human plasma was preliminarily incubated with various inflammatory mediators and filtered in a closed loop circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Malard et al of Baxter, Meyzieu, France evaluated in vitro how different membranes can remove mediators associated with the pathology of atherosclerosis using a closed loop dialysis model. They performed hemofiltration using three different membrane materials.…”
Section: Renal Supportmentioning
confidence: 99%
“…Malard et al of Baxter, Meyzieu, France evaluated in vitro how different membranes can remove mediators associated with the pathology of atherosclerosis using a closed loop dialysis model. They performed hemofiltration using three different membrane materials.…”
Section: Renal Supportmentioning
confidence: 99%
“…Adsorption could be an effective technique for the removal of large toxins as convective and diffusive techniques will always be limited by membrane permeability. Indeed, it demonstrates a real impact on the removal of plenty of atherosclerotic-linked markers [16] . Nevertheless, its evaluation remains difficult to assess and standardize.…”
Section: How To Improve Lmm Clearance?mentioning
confidence: 99%
“…Although mechanistic studies of cytokine binding, including HMGB1, to adsorptive membranes have received attention and are urgently needed, 9 few studies have focused on the adsorption mechanism. 7 In this study, we hypothesized that adsorbed heparin on an AN69ST membrane surface might contribute to HMGB1 adsorption owing to the presence of a heparin-binding site on HMGB1. We also hypothesized that the filtration rate may increase the adsorption sites by pushing the molecules deeper from membrane surface into the bulk layer.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently we reported that an AN69ST hemofilter adsorbed cytokines (IL-1β, IL-8, and IL-10), which had been elevated by LPS, from fresh porcine blood. 6 Several studies have postulated that the AN69ST membrane adsorbs cytokines via electrostatic attraction between its anionic sulfonate group and the cationic amino group of the cytokines 7,8 ; however, the specific mechanism remains unknown. Although mechanistic studies of cytokine binding, including HMGB1, to adsorptive membranes have received attention and are urgently needed, 9 few studies have focused on the adsorption mechanism.…”
Section: Introductionmentioning
confidence: 99%